1995
DOI: 10.1902/jop.1995.66.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Repair in Dogs: Recombinant Human Bone Morphogenetic Protein‐2 Significantly Enhances Periodontal Regeneration

Abstract: This study evaluated bone and cementum regeneration following periodontal reconstructive surgery using recombinant human bone morphogenetic protein-2 (rhBMP-2) in six beagle dogs. Surgically created mandibular supraalveolar premolar tooth defects in contralateral jaw quadrants were randomly assigned to receive rhBMP-2 or control vehicle. Clinical defect height was prepared to 5 mm. rhBMP-2 was applied with synthetic bioerodable particles and autologous blood using 20 micrograms rhBMP-2 per 100 microliters impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
223
2
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(254 citation statements)
references
References 47 publications
21
223
2
8
Order By: Relevance
“…The results of this study provide evidence of the safety and technical feasibility of TEB for maxillary sinus floor augmentation and vertical ridge augmentation in agreement with those from earlier animal studies that have indicated that treatment with TEB dose not result in toxicity, significant immunologic reactions, or other serious adverse effects [20][21][22][23] .…”
Section: Figsupporting
confidence: 88%
“…The results of this study provide evidence of the safety and technical feasibility of TEB for maxillary sinus floor augmentation and vertical ridge augmentation in agreement with those from earlier animal studies that have indicated that treatment with TEB dose not result in toxicity, significant immunologic reactions, or other serious adverse effects [20][21][22][23] .…”
Section: Figsupporting
confidence: 88%
“…BMPs -2, -4, -7 and -12 have all been evaluated for periodontal and peri-implant bone regeneration [67]. From this group of proteins, BMP-2 has been the most studied for bone and periodontal regenerative treatment [101][102][103][104][105][106].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…However, reports of clinical studies have not yet been published. In dental research, BMPs have been used to stimulate periodontal wound healing in dogs, with good result (175,176); again, clinical studies are, as yet, lacking. These animal studies still indicate that BMPs have possibilities for clinical use other than bone repair alone.…”
Section: Other Areas Of Potential Clinical Use Of Bmpsmentioning
confidence: 99%